IMPLEMENTASI SISTEM INFORMASI PENDAFTARAN YUDISIUM PADA STMIK STIKOM INDONESIA - I Putu Gede Budayasa; I Putu Adi Pratama; I Made Surendra (Joutica, 2019)
STMIK STIKOM Indonesia is an educational institution that routinely organizes judiciaries. In the process, the judiciary is held every 3 (three) months, STMIK STIKOM Indonesia has and runs a mechanism that involves a computer-based information system. This system is used as a media for registration for students who will join the Judiciary. The mechanism that starts from the registration process through the information system is then followed by verification and validation by several structural officials as stakeholders. For 15 (fifteen) times of implementation until March 2018, the judiciary mechanism has several weaknesses. Although registration is done through an information system, the verification and validation process by structural officials is carried out in a paper-based manner. This raises problems in terms of efficiency, filing documents for all student submissions, and the difficulties students encounter when structural officials are not in place. Better mechanisms for registration, verification and validation of judiciary data are needed, as well as a system that allows the entire process to be done in a computerized manner.